Efektivitas Kemampuan Berbicara Mahasiswa pada Vlog Youtube: Perspektif Linguistik - Rini Indah Sulistyowati; Enggar Dhian Pratamanti; Ganda Januarta; Linda Novasari (CV. Alim's Publishing, 2026)
Speaking ability is a productive language skill that emphasizes accurate pronunciation, appropriate language structures, meaningful expression, and the suitability of language use in communication contexts. It involves mastery of phonological, morphological, syntactic, semantic, and pragmatic aspects in oral communication. This study aims to: (1) describe students’ speaking ability in YouTube vlogs from a linguistic perspective; and (2) examine the effectiveness of the findings for learning, particularly in the development of digital media-based speaking instruction. The study employed a descriptive qualitative method because it focused on understanding the characteristics of students’ speaking ability in digital communication rather than conducting quantitative measurement. Data were collected through observation and note-taking techniques by carefully and repeatedly examining students’ YouTube vlog videos to identify utterances reflecting speaking ability. The identified utterances were transcribed and recorded in coding sheets to facilitate systematic data organization. The data consisted of words, phrases, clauses, sentences, and oral discourse representing the use of phonological, morphological, syntactic, semantic, and pragmatic aspects. Data analysis followed the Miles and Huberman model, including data reduction, data classification, and interpretation. Relevant data were selected and categorized according to linguistic aspects, then interpreted to explain how students’ speaking ability was demonstrated through digital communication in vlogs. The findings are expected to provide a clear description of students’ speaking ability in YouTube vlogs and to highlight the effectiveness of vlogs as a digital medium for supporting speaking instruction and enhancing students’ oral communication skills in contemporary learning environments.